Variability of the human immunodeficiency virus type 1 polymerase gene from treatment naïve patients in Accra, Ghana - Sagoe, K.W.C.; Dwidar, M.; Lartey, M.; Boamah, I.; Agyei, A.A.; Hayford, A.A.; Mingle, J.A.A.; Arens, M.Q. (Journal of Clinical Virology, 2007)
Background: Little is known about the HIV-1 drug resistance mutations in Ghana. Objectives: To determine the background protease (PR) and reverse transcriptase (RT) mutations of HIV-1 from treatment naïve patients in Ghana. Study design: Twenty-five plasma samples randomly selected were analyzed for drug resistance mutations. The molecular phylogeny and recombinant patterns of the polymerase gene of HIV-1 were also analysed. Results: No major drug-resistance mutations were seen in protease or reverse transcriptase genes. The L10I, L10V, V11I and E35G minor mutations were seen in four patients, while the V179E was observed in a patient with subtype G. An insertion of lysine was found at codon 36 of the protease gene of one patient. The predominant subtype was the CRF02_AG strain (n = 22), but 3 (13.6%) of these were recombinants with HIV-1 subtype K and/or A1. Two patients harboured unclassified/complex strains with D/CRF01_AE and G/CRFAG_02 subtypes for the PR and RT, respectively, using the Stanford Database. Viral loads (VL) ranged from 2290 to >1,500,000 c/ml (mean = 339,065 c/ml). Conclusions: Treatment naïve patients in Ghana before scale-up may have minor but not major PR mutations and high viral loads. The clinical effects of minor mutations/polymorphisms in the PR and RT genes and recombinants need to be investigated. © 2007 Elsevier B.V. All rights reserved.
Keywords: Drug resistance mutations; Ghana; HIV-1; Polymerase gene; Recombinant; Subtype; Treatment naïve